Pulmonary Embolism As a Consequence of Ultrasonographic Examination of Extremities for Suspected Venous Thrombosis: A Systematic Review - Mehdipoor, Ghazaleh; Shabestari, Abbas Arjmand; Lip, Gregory Y. H.; Bikdeli, Behnood (Seminars in Thrombosis and Hemostasis, 2016)
Ultrasonographic examination for deep vein thrombosis (DVT) appears to be a safe diagnostic method, but a theoretical concern has been raised for dislodgment of thrombi during examination. We conducted a systematic review of the literature to identify reports of possible or confirmed pulmonary embolism (PE) as a consequence of ultrasonographic assessment of extremities in patients with suspected DVT. We searched PubMed for studies published in English from January 1, 1960, to April 10, 2015. We included all cohort studies, case series, and case reports that described PE as a consequence of ultrasonographic assessment of extremities. We excluded studies that reported assessment of areas other than extremities. We screened 3,626 articles, 15 of which reported the issue of clot dislodgement and embolization following ultrasonographic examination of the extremities, including 8 original case reports (7 men and 1 woman). DVTs were in the lower extremities in all eight cases: five in right and three in left lower extremity. In six cases, the femoral veins were involved, and a free-floating thrombus was reported in two cases. Compression ultrasonography was used in all cases, with or without adjunct techniques. Overall, there were seven confirmed and one probable PE cases, two of which had fatal outcomes. Clot embolization is a rare but potential complication of ultrasonic examination for DVT that can lead into PE. Radiologists and clinicians should be aware of this potentially serious phenomenon and avoid excessive pressure when performing ultrasonographic studies of the extremities.
Keywords: pulmonary embolism; venous thrombosis; extremities; complications; ultrasonography